(untitled) (Publications Office, 2023)
The need for constant transformation and adaptation shapes the direction of institutions and critical thinking in Latin America, a premise that serves as the central theme of the seventh issue of Andina magazine. This volume offers an in-depth exploration of the region’s academic, social, and legal reinvention, examining how spaces of knowledge and governance respond to the demands of a constantly changing environment. This technological advancement goes beyond the mere digitization of content to become a space for fluid debate, collaboration, and strategic response to the profound lessons in adaptability bequeathed by the pandemic.